Pendidikan Karakter Berbasis Budaya Spiritual di SD Sathya Sai Denpasar - Putra Jaya, Maha; Sudarsana, I Ketut (Jayapangus Press, 2024)
Character is the result of education and learning from physical and spiritual knowledge obtained from school and family. The education provided by teachers at school will have an influence on students, therefore the role of teachers, parents and the environment plays a very important role in character formation. The educational process in schools based on spiritual culture will determine a lot of a child's progress in learning for the rest of his life and understanding the meaning of life for life. The aim of this research is to find out more about the spiritual culture implemented at Sathya Sai Elementary School in instilling character education values at school. This type of research is qualitative. The data collection methods used in this research are interviews, observation, literature study by analyzing data descriptively qualitatively. The location chosen in this research was Sathya Sai Elementary School. Primary data sources were obtained through interviews with several informants and secondary data were obtained through documentation and literature study. Determining informants using purposive sampling. The research results show, first: the application of spiritual culture is used and implemented because it aims to instill religious teachings as a basic concept of education which is carried out by starting from example, habituation and strengthening to students. Second, a form of education based on spiritual culture in the form of sitting in silence, satya, dharma, ahimsa, prema and santi. Third, the impact of education based on spiritual culture in the form of discipline, honesty and religion on students at school and at home.